Pengaruh Product, Price, Place, Promotion, dan Proccess terhadap Mahasiswa dalam Menentukan Pilihan Prodi Manajemen di FEB UNIBI - Anang Bambang Pujianto; Aggi Panigoro; Muhamad Deni Johansyah (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
This study identifies the influence and measures the influence of marketing mix on student decisions to choose management study programs. The sample selected is random sampling of 76 respondents using multiple linear regression analysis. Partial results of Product, Price, Place & Promotion have no influence on student decisions in determining the choice of management study programs it can from the t-count < t-table. Proccess has a positive influence on the student decision in choosing management study programs from the t-count > t-table. The simultaneous results of Product, Price, Place, Promotion & Process, simultaneously have a positive influence on student decisions in determining the choice of management study program from the f-count > f-table. Adjusted R2 value is 0.184 or 18.4, it means the marketing mix component affects the component of student decisions in choosing management study programs is 18.4%, while the remaining 81.6% of other things have not been studied.